Chapter The Ethical and Responsibility Components in Environmental Challenges: Elements of Connection between Corporate Social Responsibility and Social Impact Assessment - Coscia, Cristina (InTechOpen, 2020)
The contribution constitutes a first exploratory outcome of an ongoing research by the Author on the issues of ethics and responsibility in investment processes, starting from the assumptions of the CSR approach. It makes a critical reinterpretation of it in the light of the ongoing debates and provides a specific reading key. In this sense, the contributions of other approaches and disciplines, in particular those of social investing and social impact axis, have highlighted some issues that constitute operational steps certainly at the center of future research developments and in particular linked to current environmental challenges: 1) the creation of value, 2) the stakeholders and corporate social citizenship, 3) the shared accountability, starting from the Social Report and Participatory Budget models. Specific paragraphs are dedicated to these research issues, which are intended to highlight both the impact assessment models and the technical steps yet to be explored. As a conclusion of the reasoning and to signal potential future developments, some application areas are cited (e.g. those of urban and peri-urban regeneration processes), in which the investment assessment and impact assessment models have experimented with innovation factors, linked to the aspects of the ethics and social responsibility among stakeholders.